Calciphylaxis Mimicking Penile Gangrene: A Case Report - Tanweer Ahmed Naweed Bhatty; Kamran Riaz (The Scientific World Journal)
Calciphylaxis is a rare, but life-threatening, disease, mostly seen in patients with renal failure, especially those undergoing dialysis. It is characterized by violaceous tender areas of cutaneous plaques, necrosis, and eschar formation, mostly involving toes and fingers, but rarely the penis. Peripheral pulses are mostly preserved. The parathyroid hormone (PTH) level is elevated, along with raised calcium phosphorus product. There is radiological evidence of blood vessel and soft tissue calcification. Predisposing factors are obesity and diabetes. It is rarely encountered by a urologist and closely resembles penile gangrene.